Effect of olive pomace as supplement on growth, carcass and meat characteristics of Karadi lambs - SHAWNM SALIH; AYAD MAHMOOD (Indian Journal of Animal Sciences, 2023)
This investigation aims to determine the effect of olive pomace on growth performance and quality of carcass characteristics of Karadi lambs. Lambs were grouped by initial body weights (29.746±1.49 kg) and randomly distributed into five groups. While one group received commercial concentrates without olive pomace, the second, third, fourth and fifth groups received an experimental diet containing 4, 8, 12 and 16% of olive pomace, respectively. The lambs’ body weight, feed intake and feed conversion ratio were recorded weekly. At 46 kg live body weight, three lambs from each group were slaughtered in order to record carcass and non-carcass characteristics. Lambs fed olive pomace had significantly higher average daily gain and feed conversion ratio than those fed on the control diet. The experimental groups also produced carcass yield mainly due to an increase in carcass weight. Lambs fed 12% olive pomace had significantly higher rib eye area and fat thickness. The wholesale cuts showed that lambs fed olive pomace had significantly higher shoulder and shank percentage and significantly lower loin percentage than those of the lambs fed on the control diet. Most carcass cuts of lambs fed 8% olive pomace recorded significantly higher percentage of lean. Overall, supplementation with olive pomace significantly improved lamb growth and showed its capacity for meat production.